Climate change: fiscal and international trade issues—introduction - Büttner, Thiess; Kotsogiannis, Christos (International Tax and Public Finance, 2013)
The challenges to dealing with climate change are broad and complex. This special section reviews some of-but also brings new insights to-the challenges. © 2013 Springer Science+Business Media New York.
WiSo-Import:2015-03-26:4961
Keywords: Adaptation; Environmental uncertainty; Global externality; International trade; Mitigation